Groundwater–Stream Connectivity Mediates Metal(loid) Geochemistry in the Hyporheic Zone of Streams Impacted by Historic Mining and Acid Rock Drainage - Hoagland, Beth; Navarre-Sitchler, Alexis; Cowie, Rory; Singha, Kamini (Frontiers in Water, 2020)
High concentrations of trace metal(loid)s exported from abandoned mine wastes and acid- rock drainage pose a risk to the health of aquatic ecosystems. To determine if and when the hyporheic zone mediates metal(loid) export, we investigated the relationship between streamflow, groundwater-stream connectivity, and subsurface metal(loid) concentrations in two ~1 km stream reaches within the Bonita Peak Mining District, a U.S. Environmental Protection Agency Superfund site located near Silverton, Colorado, USA. The hyporheic zones of reaches in two streams—Mineral Creek and Cement Creek—were characterized using a combination of salt-tracer injection tests, transient-storage modeling, and geochemical sampling of the shallow streambed (< 0.7 m). Based on these data, we present two conceptual models for subsurface metal(loid) behavior in the hyporheic zones, including (1) well-connected systems characterized by strong hyporheic mixing of infiltrating stream water and upwelling groundwater and (2) poorly connected systems delineated by physical barriers that limit hyporheic mixing. The comparatively large hyporheic zone and high hydraulic conductivities of Mineral Creek created a connected stream-groundwater system, where mixing of oxygen-rich stream water and metal-rich groundwater facilitated the precipitation of metal colloids in the shallow subsurface. In Cement Creek, precipitation of iron-oxides at depth (~0.4 m) created a low hydraulic-conductivity barrier between surface water and groundwater. Cemented iron-oxides were an important regulator of metal(loid) concentrations in this poorly connected stream-groundwater system due to the formation of strong redox gradients induced by a relatively small hyporheic zone and high fluid residence times. Comparison of the conceptual models to stream concentration-discharge relationships exhibited a clear link between geochemical processes occurring within the hyporheic zone of the well-connected system and export of particulate Al, Cu, Fe, and Mn, while the poorly connected system did not have a notable influence on metal concentration-discharge trends. Mineral Creek was an example of a hyporheic system that serves as a natural dissolved metal(loid) sink, whereas poorly connected systems such as Cement Creek may benefit more from subsurface remediation than surface-water treatment to mitigate metal export.